Equality against hierarchy: Imagining modernity in subaltern India - Roy, I (SAGE Publications, 2016)
How do subalterns imagine their membership in India’s political community? Many scholars argue that they imbibe the egalitarian ideals in India’s political-economic sphere. Others suggest that subalterns identify the modernising impulses of the political-economic sphere as a greater threat to their ways of life. Intervening in this debate, recent research enlivens analysts to the perspective that the political-economic sphere of the state cannot be unambiguously mapped onto modernity. Nor, for that matter, can the sociocultural sphere be regarded as singular realm of uninterrupted tradition. This article is offered as a contribution to this strand of the scholarship. By exploring endogenous egalitarian impulses among subaltern groups in India, I seek to interrogate the widely prevailing notion that ideas associated with modernity are the preserve of and emanate from elites in the political-economic sphere of the Indian state. Subalterns eschew notions of hierarchy and value ideas of equality and social justice without necessarily drawing on statist vocabularies in their assertions.